2017
DOI: 10.1152/ajpheart.00163.2017
|View full text |Cite
|
Sign up to set email alerts
|

Acute beetroot juice supplementation on sympathetic nerve activity: a randomized, double-blind, placebo-controlled proof-of-concept study

Abstract: Acute dietary nitrate ([Formula: see text]) supplementation reduces resting blood pressure in healthy normotensives. This response has been attributed to increased nitric oxide bioavailability and peripheral vasodilation, although nitric oxide also tonically inhibits central sympathetic outflow. We hypothesized that acute dietary [Formula: see text] supplementation using beetroot (BR) juice would reduce blood pressure and muscle sympathetic nerve activity (MSNA) at rest and during exercise. Fourteen participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
61
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 50 publications
4
61
0
2
Order By: Relevance
“…Also, evidence exists that acute nitrate supplementation is effective at reducing muscle sympathetic nerve activity at rest (Notay et al . ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Also, evidence exists that acute nitrate supplementation is effective at reducing muscle sympathetic nerve activity at rest (Notay et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…This is plausible considering that past work finds chronic Cit increases urinary excretion of cyclic GMP (Schwedhelm et al 2008), a byproduct of NO-stimulated guanylyl cyclase in smooth muscle that results in vasodilatation. Also, evidence exists that acute nitrate supplementation is effective at reducing muscle sympathetic nerve activity at rest (Notay et al 2017).…”
Section: Effect Of L-citrulline On Blood Pressurementioning
confidence: 99%
“…2009; Notay et al . 2017). However, no change in plasma nitrite levels were previously reported in healthy subjects during a 60 min inhalation of 25 ppm iNO (Westfelt et al .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we did not observe a significant relationship between the change in S pO 2 and change in MSNA (r = −0.16, P = 0.61) in the present study. Finally, whilst any NO that enters the circulation is rapidly inactivated (Rimar & Gillis, 1993), an increased central NO bioavailability, via the nitrate-nitrite-NO pathway, may have influenced the MSNA response (Owlya et al 1997;Young et al 2009;Notay et al 2017). However, no change in plasma nitrite levels were previously reported in healthy subjects during a 60 min inhalation of 25 ppm iNO (Westfelt et al 1995).…”
Section: Sympathetic Neural Activation By Pulmonary Arterial Barorecementioning
confidence: 96%
“…There are also studies that do not show any BP reduction after nitrate-rich BRJ supplementation de Vries and DeLorey 2019;Notay, Incognito, and Millar 2017;Perez et al 2019). de Vries & DeLorey (2019) found that sympathetic vasoconstrictor responsiveness was not altered, not in rest not after exercise, after a single dose of BRJ consumption compared to placebo (de Vries and DeLorey 2019).…”
Section: Effect On Blood Pressurementioning
confidence: 99%